METHODOLOGY FOR IMPROVING THE TECHNICAL TRAINING OF YOUNG BOXERS (World Bulletin of Management and Law, 2024)
In this article, we will show you a number of necessary instructions and recommendations on the current problems of young boxers at the time of technical training, as well as on the way to finding their solution. This article also covers the analysis of the technical training levels of young boxers.